Research on Learners' Personality Mining Based on Improved Decision Tree Algorithm - Qiang Yang; Jianli Wang (2008 Second International Conference on Genetic and Evolutionary Computing : 25-26 September 2008, 2008)
In order to truly realize the personalized learning in which learners are looked as the main characters, we should focus on the characteristics of learners. In order to obtain the characteristics of learners, we should mine the characteristics of learners. In this paper we put forward a kind of data mining algorithm based on improved decision tree, and combined with the characteristics data of personalized learning, then we simple analyze the application of the decision tree algorithm in the learners' personalized mining.